Design and Implementation of Multiplexed and Obfuscated Physical Unclonable Function - Mohd Syafiq Mispan; Hafez Sarkawi; Aiman Zakwan Jidin; Radi Husin Ramlee; Haslinah Mohd Nasir (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
Model building attack on Physical Unclonable Functions (PUFs) by using machine learning (ML) techniques has been a focus in the PUF research area. PUF is a hardware security primitive which can extract unique hardware characteristics (i.e., device-specific) by exploiting the intrinsic manufacturing process variations during integrated circuit (IC) fabrication. The nature of the manufacturing process variations which is random and complex makes a PUF realistically and physically impossible to clone atom-by-atom. Nevertheless, its function is vulnerable to model-building attacks by using ML techniques. Arbiter-PUF is one of the earliest proposed delay-based PUFs which is vulnerable to ML-attack. In the past, several techniques have been proposed to increase its resiliency, but often has to sacrifice the reproducibility of the Arbiter-PUF response. In this paper, we propose a new derivative of Arbiter-PUF which is called Mixed Arbiter-PUF (MA-PUF). Four Arbiter-PUFs are combined and their outputs are multiplexed to generate the final response. We show that MA-PUF has good properties of uniqueness, reliability, and uniformity. Moreover, the resilient of MA-PUF against ML-attack is 15% better than a conventional Arbiter-PUF. The predictability of MA-PUF close to 65% could be achieved when combining with challenge permutation technique.